The Interaction of Australian Winter Monsoon and East Asian Summer Monsoon and Its Impacts on Convergence Around Kalimantan - Ayu Vista Wulandari; Rira Angela Damanik; Rosi Hanif Damayanti; Vinca Amalia Rizkiafama; Juni Tika Simanjuntak; Nurjanna Joko Trilaksono (Journal of Engineering Technology and Applied Physics)
The Australian Winter Monsoon (AWM) and East Asian Summer Monsoon (EASM) play a crucial factor in altering the global climate. The two monsoons are closely linked to each other through cross-equatorial flow. As the Australian High anomaly increases, the Western Pacific Subtropical High (WPSH) also increases, resulting in an anticyclone anomaly in Australia and the Western Pacific region that intensifies the AWM and EASM. This study examines the effect of variations between the two monsoons by removing ENSO and IOD signals on meteorological parameters in the Kalimantan region. European Center for Medium-Range Weather Forecasts (ECMWF) Reanalysis v5 data with a resolution of 0.25° × 0.25° is used to examine the effect at the local scale and rainfall data from local observations for 35 years in the June-July-August (JJA) or boreal summer. Composite and correlation analyses were conducted by calculating the regression coefficients between the composite variables and the target variables. The EASM and AWM were also analyzed using Singular Value Decomposition (SVD) to identify the most relevant spatial patterns. This research reveals that when the AWM and EASM increase at once, two connected anticyclone anomalies over the maritime continent trigger easterly wind anomalies, leading to convergence in Kalimantan, which increases the rainfall intensity in the Kalimantan region.